The estrogen–brain interface in neuroinflammation: a multidimensional mechanistic insight - Lu, Jie; Xian, Tie-Jun; Li, Cheng-Jun; Wang, Yang (Frontiers in Aging Neuroscience, 2025)
Neuroinflammation plays a dual role in the central nervous system, offering protection in acute phases but contributing to chronic damage in neurodegenerative diseases. Estrogen, traditionally recognized for its reproductive functions, exerts extensive neuroprotective effects by modulating neuroinflammatory processes across multiple levels. This review explores the actions of estrogen through its receptors in astrocytes, microglia, and neurons, emphasizing its regulation of signaling pathways such as PI3K/Akt, NF-κB, and WNT/β-catenin. Estrogen also enhances mitochondrial function, promotes DNA repair, and interacts with the gut microbiota to influence systemic inflammation. Furthermore, sex-specific responses to 17α-estradiol highlight the importance of hormonal context. Together, these findings underscore estrogen’s potential as a multifaceted modulator of neuroinflammation and provide insight for precision therapeutic strategies.